2016
DOI: 10.1126/science.aag1322
|View full text |Cite
|
Sign up to set email alerts
|

Potent protection against H5N1 and H7N9 influenza via childhood hemagglutinin imprinting

Abstract: Two zoonotic influenza A viruses (IAV) of global concern, H5N1 and H7N9, exhibit unexplained differences in age distribution of human cases. Using data from all known human cases of these viruses, we show that an individual’s first IAV infection confers lifelong protection against severe disease from novel hemagglutinin (HA) subtypes in the same phylogenetic group. Statistical modeling shows protective HA imprinting is the crucial explanatory factor, providing 75% protection against severe infection and 80% pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
377
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(393 citation statements)
references
References 64 publications
(78 reference statements)
14
377
1
1
Order By: Relevance
“…In recent years, avian influenza virus H5N1 and H7N9 subtypes have caused hundreds of human infections with a mortality rate of 20% to 60% [9]. Studies have demonstrated that “original antigenic sin” [138] is a key determinant for the susceptibility of zoonotic influenza viruses [138–140]. “Original antigenic sin” arises when our immune system employs immunological memory based on an earlier infection by a virus with an slightly different antigenicity, which then skews the current immune response towards antibodies that were previously produced and to epitopes recognized during previous infections [138].…”
Section: Protective Immunity Against Zoonotic Influenza Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, avian influenza virus H5N1 and H7N9 subtypes have caused hundreds of human infections with a mortality rate of 20% to 60% [9]. Studies have demonstrated that “original antigenic sin” [138] is a key determinant for the susceptibility of zoonotic influenza viruses [138–140]. “Original antigenic sin” arises when our immune system employs immunological memory based on an earlier infection by a virus with an slightly different antigenicity, which then skews the current immune response towards antibodies that were previously produced and to epitopes recognized during previous infections [138].…”
Section: Protective Immunity Against Zoonotic Influenza Virusesmentioning
confidence: 99%
“…Based on statistical modeling, such childhood imprinting is also important for determining the susceptibility against emerging avian influenza viruses H5N1 and H7N9 subtypes [140]. Briefly, those who were infected with seasonal H1 or H2 subtype (group 1) during their first encounter of influenza virus are less susceptible to H5 viruses (group 1), whereas those who were infected with seasonal H3 subtype (group 2) during their first encounter of influenza virus are less susceptible to H7 viruses (group 2) [140]. Overall, these observations highlight the importance of “original antigenic sin” in protection against zoonotic influenza viruses.…”
Section: Protective Immunity Against Zoonotic Influenza Virusesmentioning
confidence: 99%
“…Such Th17 memory responses may help protect the lungs against serotypes of pneumococcus that are not in vaccines or the previous experience of that individual. In humans, immunological “imprinting” from first influenza infections in childhood was observed to help prevent severe pneumonia from multiple sub-types within that phylogenetic group but not from other phylogenetic groups (e.g., H1 infections are good for later infections with H2 or H5 but not H3 or H7, whereas H3 is good against subsequent H7 but not H1, H2, or H5 infections) (22). Such heterotypic protection that results from first infections may explain some of the variations across differently aged cohorts to severe infections from different strains of influenza.…”
Section: Advances In Immune Resistancementioning
confidence: 99%
“…Pneumonia defense is strongly influenced by the earliest infections with respiratory pathogens, based on evidence of immunological "imprinting" against influenza viruses (167). Those born before 1968 were likely first infected with influenza viruses containing hemagglutinins (HAs) from phylogenetic group 1 (which includes H1, H2, and H5 HAs), whereas those born after that date were more likely to be first infected by influenza viruses with group 2 HAs (which includes H3 and H7 HAs).…”
Section: A Naturally Acquired Heterotypic Adaptive Immunitymentioning
confidence: 99%